Ineffectiveness of Vi and chemically treated endotoxins as typhoid vaccines in mice challenged with a Salmonella typhosa-Salmonella typhimurium hybrid. - Diena, B B (1975)
Purified Vi antigen, acetic anthydride-treated Salmonella typhosa endotoxin, and potassium methylate-treated S. typhosa endotoxin employed as vaccines in Swiss white mice failed to protect these animals against challenge with a virulent S. typhimurium hybrid expressing S. typhosa antigens.